Ribosomal, Telomere, and Mitochondrial Repeat Copy Number Variations in Female Genomes during Ovarian Stimulation and the Prediction of In Vitro Fertilization Outcome: A Pilot Study - Natalia Nikolaevna Veiko; Elizaveta Sergeevna Ershova; Lev Nikolaevich Porokhovnik; Maria Petrovna Klimenko; Peter Afanasievich Klimenko; Pavel Evgenievich Umriukhin; Еdmund Viktorovich Kostyuk; Mark Arkadievich Kurtser; Oksana Nikolaevna Agafonova; Tatyana Agaragimovna Salimova; Sergey Ivanovich Kutsev; Vera Leonidovna Izhevskaya; et al. (Frontiers in Bioscience-Scholar, 2023)
Introduction: Individual risk assessment of assisted reproductive technologies is essential for personalized treatment strategies. Genetic and genomic indicators of the response to stress by cells could provide individual prognostic indicators for in vitro fertilization (IVF) success. Such indicators include the copy number of ribosomal genes (rDNA), which modulates the level of protein synthesis, and the abundance of mitochondrial DNA (mtDNA), which provides the cell with energy, while the content of telomere repeats (TRs) indicate the biological age. Materials and Methods: The contents of the three repeats in DNA isolated from blood leukocytes of 40 women before and after ovarian stimulation were assayed prior to IVF. Then, we divided the women into a successful IVF group, IVF+ (N = 17, 7 cases of twins), and a group of failed cases, IVF– (N = 23). The control group included 17 non-pregnant women with natural childbirth in the past. The nonradioactive quantitative hybridization (NQH) method was applied to assay the genome repeat contents. Results: The number of rDNA copies in the IVF+ group was significantly higher than in the IVF– group (p < 10-8). The number of mtDNA copies in the IVF+ group also exceeded those in the IVF– group (p < 0.001), whereas the TR content in the two groups differed, albeit, non-significantly (p < 0.03). Following the ovarian stimulation, the rDNA copy numbers did not change, while the contents of the mtDNA and TR varied significantly. Conclusions: This pilot study has shown that rDNA abundance in blood leukocytes can be considered a stable and effective predictor. Very low numbers of ribosomal repeat copies (<330) entail a high risk of IVF failure. However, a combination of numerous mtDNA and TRs, provided that rDNA content is not very low, increases the probability of multiple pregnancies.